Movement ecology of a West African sciaenid fish, Argyrosomus coronus, in southern Angola - Parkinson, Matthew Cameron (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science)
Argyrosomus coronus is a large sciaenid species with a primary distribution between Cape Frio, in Namibia, and Luanda, in Angola, where it exists as a panmictic stock. Early juveniles (< 300 mm TL) occur on muddy offshore substrata (50"“80 m deep) and at one year of age they recruit into the inshore zone. Adults are thought to predominantly occur inshore. Spawning occurs in the species during late spring. The species is heavily targeted by the recreational, subsistence, artisanal and commercial fisheries as juveniles through to adults and there are signs of population decline with declines in catch per unit effort (CPUE) and maximum size. A basic understanding of their movement ecology has emerged from previous studies, based on conventional tagging (mark-recapture) and CPUE monitoring from a shore-based recreational fishery. Juveniles were thought to be resident, with larger fish undertaking long distance migration southward in the austral summer and returning during the austral winter. In addition to the fishery-related threats faced by the species, the southern Angolan region has been identified to be an ocean warming hotspot, and this has been linked to a southward distribution shift and the recent hybridisation of A. coronus with its congener A. inodorus, in Namibia. This study aims to expand the knowledge of the movement ecology of A. coronus and to interrogate our current understanding of the movement patterns of the species using passive acoustic telemetry. Passive acoustic receivers were deployed at three study sites, Flamingo, where all tagging occurred, which lies ~ 200 km north of the Angolan border with Namibia, is a relatively exposed stretch of coastline; Tombua Bay, which lies 30 km south of Flamingo, is a small, sheltered natural embayment; and Baia dos Tigres, which lies 100 km south of Tombua Bay, is a sheltered lagoon in the lee of an island ~ 10 km from the mainland. Tagging occurred in two batches, one year apart. In the first batch, sub-adults (n = 3) and adults (n = 17) were tagged and monitored for two years. In the second batch, juveniles (n = 7) and sub-adults (n = 3) were tagged and monitored for one year. The first objective of this
Keywords: Argyrosomus coronus -- Benguela Current -- Geographical distribution; Underwater acoustic telemetry; Fisheries -- Benguela Current; Fish populations; Spatio-temporal dynamics; Spatial ecology